The Yoráubâa traditional healers of Nigeria - Adekson, Mary Olufunmilayo (African studies (Routledge (Firm)), 2003)
This work examines the counseling approaches and techniques used by Yoruba traditional healers of Nigeria. It also describes the functions performed by Yoruba traditional healers when they work within the Yoruba cultural milieu. The information elicited from Yoruba traditional healers through videotape and interviews was analyzed by a Nigerian woman from the Yoruba ethnic group. The results of the volume support the premise that culture plays a significant role in the kind of healing methods and counseling techniques used by professionals and traditional healers, as well as in the type of prof.